Assessing the Critical Success Factors for Aquaculture Enterprise Development in South Africa - Brown-Webb, Bernadette; Nesamvuni, Azwihangwisi E.; de Bruyn, Melanie; van Niekerk, Johan A.; Pillay, Parsuramen (Technium Social Sciences Journal, 2022)
In South Africa, small enterprise development is an important strategy for the economic growth, transformation and eradication of poverty and inequality. The government also promotes the development of the aquaculture sector to provide food security, contribute to wealth and job creation, provide livelihood opportunities, and contribute to transformation. South African businesses unfortunately have a low rate of business sustainability. This study investigated the critical success factors enabling aquaculture enterprises in South Africa to become self-sustainable, and the potential reasons for failure including those enterprises that received public funding. The study was conducted on the West Coast of the Western Cape, South Africa. A multiple-case study approach was followed, focusing on the marine mussel farming sub-sector in Saldanha Bay. Semi-structured interviews were conducted with the owners or managers of ten mussel farming enterprises, and with nine representatives of role players with responsibility or experience in aquaculture, agriculture, or enterprise development. The results of the study indicated that aquaculture farmers and role players have a similar understanding of the concept of self-sustainability in aquaculture agribusinesses, especially the need for profitability and independence. The most critical success factors for self-sustainable aquaculture enterprises include environmentally responsible and sustainable farming practices, efficiently addressing economic challenges and opportunities, cultivating good business leadership and management, and a supportive business and enabling environment. The main reasons for failing to become self-sustainable include environmentally unsustainable farming practices, economic challenges, weak business leadership and management, and challenges related to the business and enabling environment. The paper argues that commercially focused aquaculture ventures could achieve social benefits, however, socially-focused ventures are unlikely to achieve commercial benefits. The study recommends interventions that could assist aquaculture enterprises in addressing the critical factors described in this paper, to achieve self-sustainability in the long term.